Serious Games in pre-K and K-6 education - Papanastasiou, George; Drigas, Athanasios; Skianis, Charalabos (Technium Education and Humanities, 2022)
Serious Games indicate positive effects on pre-K and K-6 students and scaffold learning in a more engaging and motivating approach. Research has shown that Serious Games provide students with variety, the potential for widening participation, and the ability to work at their own pace. Serious Games based Learning has proven its added value in almost every aspect of the curriculum knowledge, skills, and attitudes, namely, Reading, Writing and Language learning, Geometric and Mathematical thinking, Strategic and Reasoning abilities, Critical thinking, Problem solving and Creativity, Executive Control skills, Physics, Geography and Science courses.